Early contact with the criminal justice system and intellectual functioning as risk factors for violent and chronic adult offending - Thomas, Johanna M. (Western criminology review, 2014)
Prior research suggests early contact with the criminal justice system and neuropsychological deficits are associated with a life course persistent offending trajectory. Prior analyses of this important subject matter in life course criminology have primarily relied on analyses of age cohorts and samples drawn from urban areas. Moreover, prior studies have primarily examined samples comprised largely of majority group members who have committed only minor offenses. Data for the current study were collected from the institutional files of a cohort of 817 males exiting a Louisiana juvenile correctional facility in 1976. This information was then merged with data on the official adult records of participants up to 1988. Logistic and negative binomial regression models were used to examine the effects of age at first contact with the criminal justice system and neuropsychological/intellectual functioning on chronic and violent offending during early adulthood. Age at first contact with law enforcement and intellectual functioning emerged as robust predictors of both violent and chronic offending over the life course. Controlling for race, family criminal history, number of juvenile convictions, juvenile offense type, and diagnosed conduct disorders, early contact with the criminal justice system and intellectual functioning were inversely related to the likelihood of being charged with a violent offense as an adult. Further, early contact with the system and intellectual functioning exhibited strong inverse associations with the total number of adult criminal charges.